Probing thermal expansion coefficients of monolayers using surface enhanced Raman scattering. Issue 101 (18th October 2016) - Zhang, Duan; Wu, Ye-Cun; Yang, Mei; Liu, Xiao; Coileáin, Cormac Ó; Xu, Hongjun; Abid, Mourad; Abid, Mohamed; Wang, Jing-Jing; Shvets, Igor V.; Liu, Haonan; Wang, Zhi; et al.
Abstract : A non-destructive method has been proposed to probe thermal expansion coefficients of the monolayer materials using surface-enhanced Raman spectroscopy. Abstract : Monolayer transition metal dichalcogenides exhibit remarkable electronic and optical properties, making them candidates for application within flexible nano-optoelectronics, however direct experimental determination of their thermal expansion coefficients (TECs) is difficult. Here, we propose a non-destructive method to probe the TECs of monolayer materials using surface-enhanced Raman spectroscopy (SERS). A strongly coupled Ag nanoparticle over-layer is used to controllably introduce temperature dependent strain in monolayers. Changes in the first-order temperature coefficient of the Raman shift, produced by TEC mismatch, can be used to estimate relative expansion coefficient of the monolayer. As a demonstration, the linear TEC of monolayer WS2 is probed and is found to be 10.3 × 10 −6 K −1, which would appear support theoretical predictions of a small TEC. This method opens a route to probe and control the TECs of monolayer materials.